The Roles of Glutamate Receptors and Their Antagonists in Status Epilepticus, Refractory Status Epilepticus, and Super-Refractory Status Epilepticus - Tzu-Hsin Huang; Ming-Chi Lai; Yu-Shiue Chen; Chin-Wei Huang (Biomedicines, 2023)
Status epilepticus (SE) is a neurological emergency with a high mortality rate. When compared to chronic epilepsy, it is distinguished by the durability of seizures and frequent resistance to benzodiazepine (BZD). The Receptor Trafficking Hypothesis, which suggests that the downregulation of γ-Aminobutyric acid type A (GABAA) receptors, and upregulation of N-methyl-D-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors play major roles in the establishment of SE is the most widely accepted hypothesis underlying BZD resistance. NMDA and AMPA are ionotropic glutamate receptor families that have important excitatory roles in the central nervous system (CNS). They are both essential in maintaining the normal function of the brain and are involved in a variety of neuropsychiatric diseases, including epilepsy. Based on animal and human studies, antagonists of NMDA and AMPA receptors have a significant impact in ending SE; albeit most of them are not yet approved to be in clinically therapeutic guidelines, due to their psychomimetic adverse effects. Although there is still a dearth of randomized, prospective research, NMDA antagonists such as ketamine, magnesium sulfate, and the AMPA antagonist, perampanel, are regarded to be reasonable optional adjuvant therapies in controlling SE, refractory SE (RSE) or super-refractory SE (SRSE), though there are still a lack of randomized, prospective studies. This review seeks to summarize and update knowledge on the SE development hypothesis, as well as clinical trials using NMDA and AMPA antagonists in animal and human studies of SE investigations.